Flame-retardant polycarbonate resin composition and molded article thereof

The flame-retardant polycarbonate resin composition, enhanced with specific additives, addresses the issue of moisture-heat degradation by maintaining impact strength and flame retardancy, ensuring durability and performance in diverse applications.

JP7658771B2Active Publication Date: 2025-04-08TEIJIN LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021048206
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-23
Publication Date
2025-04-08
Estimated Expiration
2041-03-23

AI Technical Summary

Technical Problem

Existing flame-retardant polycarbonate resin compositions fail to adequately maintain impact strength and flame retardancy when subjected to moisture-heat degradation.

Method used

A flame-retardant polycarbonate resin composition is developed by adding an impact modifier, a phosphazene containing 98.5 mol% or more of a phosphazene cyclic trimer, an organic sulfonate metal salt, and a drip inhibitor to the polycarbonate resin, thereby enhancing impact strength and flame retardancy while suppressing degradation due to moisture-heat.

Benefits of technology

The composition achieves improved impact strength and flame retardancy, and effectively prevents the reduction of these properties due to moisture-heat degradation, ensuring durability and performance in diverse applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658771000001
    Figure 0007658771000001
  • Figure 0007658771000002
    Figure 0007658771000002
  • Figure 0007658771000003
    Figure 0007658771000003
Patent Text Reader

Abstract

To provide a flame-retardant polycarbonate resin composition which is excellent in impact strength and flame retardancy and suppresses reduction in impact strength and flame retardancy due to moist heat deterioration.SOLUTION: The flame-retardant polycarbonate resin composition contains, based on (A) 100 pts.wt. of a polycarbonate resin (component A), (B) 1-8 pts.wt. of an impact modifier (component B), (C) 1-8 pts.wt. of a phosphazene (component C) containing 98.5 mol% or more of a phosphazene cyclic trimer, (D) 0.01-0.5 pt.wt. of an organic sulfonic acid metal salt (component D), and (E) 0.05-2 pts.wt. of a drip inhibitor (component E).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flame-retardant polycarbonate resin composition and a molded article thereof. More specifically, the present invention relates to a flame-retardant polycarbonate resin composition having improved impact strength and flame retardancy and suppressed deterioration of impact strength and flame retardancy due to moist heat degradation, which is obtained by adding an impact modifier, a phosphazene containing 98.5 mol% or more of a phosphazene cyclic trimer, an organic sulfonic acid metal salt, and an anti-drip agent to a polycarbonate resin. [Background technology]

[0002] Polycarbonate resins are excellent in mechanical properties, dimensional accuracy, electrical properties, and thermal properties, and are widely used as engineering plastics in various fields such as electrical and electronic equipment, automobiles, and office automation. In recent years, as products have become smaller and lighter, products for office automation equipment and home appliances have become thinner, and materials with excellent impact strength and flame retardancy are required. In addition, due to the diversification of usage environments, including indoors and outdoors, and the improvement in the utilization rate of recycled materials through closed recycling, these products require materials that have excellent impact strength, flame retardancy, and excellent durability with little deterioration even in long-term use. In other words, materials that have excellent impact strength and flame retardancy and that do not deteriorate much due to moist heat degradation are required.

[0003] In order to solve such problems, Patent Document 1 discloses a flame-retardant polycarbonate resin composition comprising an aromatic polycarbonate resin, an impact modifier, a phosphazene containing 98.5 mol% or more of a phosphazene cyclic trimer, and an anti-drip agent. However, the desired suppression of the decrease in impact strength and flame retardancy due to moist heat deterioration was insufficient and unsatisfactory.

[0004] On the other hand, it is known that phosphazene and organic sulfonic acid metal salt are used in combination to improve impact strength and flame retardancy. Patent Document 2 discloses a flame-retardant polycarbonate resin composition consisting of a polycarbonate resin, a phosphazene, a silicone compound, an organic sulfonic acid metal salt, and an anti-drip agent. Patent Document 3 discloses a flame-retardant polycarbonate resin composition consisting of a polycarbonate resin, a phosphazene, an organic sulfonic acid metal salt, a core-shell type graft copolymer, and a fluorinated polyolefin. However, in both documents, the suppression of the decrease in impact strength and flame retardancy due to moist heat deterioration required is insufficient and not satisfactory. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2020 / 066535 publication [Patent Document 2] JP 2004-67881 A [Patent Document 3] JP 2016-84414 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above, an object of the present invention is to provide a flame-retardant polycarbonate resin composition which is excellent in impact strength and flame retardancy and in which deterioration of the impact strength and flame retardancy due to moist heat degradation is suppressed. [Means for solving the problem]

[0007] As a result of intensive research conducted by the present inventors to solve the above problems, The present inventors have discovered a method for obtaining a flame-retardant polycarbonate resin composition having improved impact strength and flame retardancy and suppressed deterioration in impact strength and flame retardancy due to moist heat degradation by adding a modifier, a phosphazene containing 98.5 mol % or more of a phosphazene cyclic trimer, an organic sulfonic acid metal salt, and an anti-drip agent, and have thus completed the present invention.

[0008] According to the present invention, the above-mentioned object is achieved by a flame-retardant polycarbonate resin composition, which comprises, relative to 100 parts by weight of (A) polycarbonate resin (component A), 1 to 8 parts by weight of (B) impact modifier (component B), 1 to 8 parts by weight of (C) phosphazene containing 98.5 mol % or more of phosphazene cyclic trimer (component C), 0.01 to 0.5 parts by weight of (D) organic sulfonic acid metal salt (component D), and 0.05 to 2 parts by weight of (E) anti-drip agent (component E).

[0009] The present invention will be described in detail below.

[0010] (Component A: polycarbonate resin) The polycarbonate resin used in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polymerization method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound.

[0011] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylene) Examples of the dihydric phenol include 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. The preferred dihydric phenol is a bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.

[0012] In the present invention, in addition to bisphenol A-based polycarbonates, which are general-purpose polycarbonates, it is possible to use special polycarbonates produced using other dihydric phenols as the A component.

[0013] For example, polycarbonates (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter sometimes abbreviated as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes abbreviated as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF") as part or all of the dihydric phenol component are suitable for applications where dimensional change due to water absorption and shape stability are particularly demanding. These dihydric phenols other than BPA can be used in the polycarbonates. It is preferable to use 5 mol % or more, particularly 10 mol % or more, of the total dihydric phenol components constituting the carbonate.

[0014] In particular, when high rigidity and better hydrolysis resistance are required, it is particularly suitable that the component A constituting the resin composition is a copolymer polycarbonate of the following (1) to (3). (1) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %). (2) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPA is 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF is 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %). (3) A copolymer polycarbonate in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).

[0015] These special polycarbonates may be used alone or in a suitable mixture of two or more kinds, or may be used in a mixture with the commonly used bisphenol A type polycarbonate.

[0016] The production methods and properties of these special polycarbonates are described in detail in, for example, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435 and JP-A-2002-117580.

[0017] Among the various polycarbonates mentioned above, those in which the copolymer composition and the like are adjusted to bring the water absorption rate and Tg (glass transition temperature) into the ranges described below have good hydrolysis resistance of the polymer itself and are also remarkably excellent in terms of low warpage after molding, and are therefore particularly suitable in fields where dimensional stability is required. (i) a polycarbonate having a water absorption rate of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180° C., or (ii) Polycarbonate having a Tg of 160 to 250° C., preferably 170 to 230° C., and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, more preferably 0.14 to 0.27%.

[0018] The water absorption rate of polycarbonate is a value measured by using a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm and measuring the moisture content after immersing it in water at 23°C for 24 hours in accordance with ISO62-1980. Also, Tg (glass transition temperature) is a value determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121.

[0019] The carbonate precursor may be a carbonyl halide, a carbonic acid diester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.

[0020] When the dihydric phenol and carbonate precursor are subjected to the interfacial polymerization method to produce the polycarbonate resin, a catalyst, a terminal terminator, an antioxidant for preventing the dihydric phenol from being oxidized, etc. may be used as necessary. The polycarbonate resin of the present invention is a branched polycarbonate resin copolymerized with a polyfunctional aromatic compound having three or more functionalities, a polyester carbonate copolymerized with an aromatic or aliphatic (including alicyclic) bifunctional carboxylic acid, The polycarbonate resins include copolymerized polycarbonate resins obtained by copolymerizing a difunctional alcohol (including alicyclic), and polyester carbonate resins obtained by copolymerizing such a difunctional carboxylic acid and a difunctional alcohol. The polycarbonate resins may also be a mixture of two or more of the polycarbonate resins obtained.

[0021] The branched polycarbonate resin can impart drip prevention properties to the resin composition of the present invention. Examples of trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0022] The constituent units derived from a polyfunctional aromatic compound in the branched polycarbonate preferably account for 0.01 to 1 mol %, more preferably 0.05 to 0.9 mol %, and even more preferably 0.05 to 0.8 mol %, based on a total of 100 mol % of the constituent units derived from a dihydric phenol and the constituent units derived from such a polyfunctional aromatic compound.

[0023] In particular, in the case of the melt transesterification method, branched structural units may be generated as a side reaction, and the amount of such branched structural units is preferably 0.001 to 1 mol %, more preferably 0.005 to 0.9 mol %, and even more preferably 0.01 to 0.8 mol %, based on the total of 100 mol % including the structural units derived from the dihydric phenol. 1 It can be calculated by H-NMR measurement.

[0024] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. Examples of the aliphatic difunctional carboxylic acid include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. The bifunctional alcohol is more preferably an alicyclic diol, such as cyclohexane dimethanol, cyclohexane diol, and tricyclodecane dimethanol.

[0025] The reaction modes of the method for producing the polycarbonate resin of the present invention, such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid-phase transesterification method, and the ring-opening polymerization method of a cyclic carbonate compound, are well known in various literatures and patent publications.

[0026] The viscosity average molecular weight (M) of the polycarbonate resin is not particularly limited, but is preferably 1.8×10 4 ~4.0×10 4 and more preferably 2.0×10 4~3.5×10 4 , and more preferably 2.2×10 4 ~3.0×10 4 The viscosity average molecular weight is 1.8 × 10 4 Polycarbonate resins with a viscosity average molecular weight of less than 4.0×10 may not provide good mechanical properties. 4 Resin compositions obtained from polycarbonate resins exceeding this limit are inferior in terms of flowability during injection molding and therefore are inferior in versatility.

[0027] The polycarbonate resin may be a mixture of polycarbonate resins having a viscosity average molecular weight outside the above range. 4 ) the entropy elasticity of the resin is improved. As a result, good molding processability is exhibited in gas-assisted molding and foam molding, which are sometimes used when molding reinforced resin materials into structural members. Such improvement in molding processability is even better than that of the branched polycarbonate. In a more preferred embodiment, component A has a viscosity average molecular weight of 7×10 4 ~3×10 5 Polycarbonate resin A-1-1-1 component) and viscosity average molecular weight 1 × 10 4 ~3×10 4 The viscosity average molecular weight of the polycarbonate resin (A-1-1-2 component) is 1.6 × 10 4 ~3.5×10 4 It is also possible to use a polycarbonate resin (A-1-1 component) (hereinafter sometimes referred to as a "polycarbonate resin containing a high molecular weight component").

[0028] In the polycarbonate resin containing a high molecular weight component (component A-1-1), the molecular weight of component A-1-1-1 is 7×10 4 ~2×10 5 is preferable, and more preferably 8×10 4 ~2×10 5 , and more preferably 1×10 5 ~2×10 5 , particularly preferably 1×10 5 ~1.6×105 The molecular weight of component A-1-1-2 is 1×10 4 ~2.5×10 4 is preferable, and more preferably 1.1×10 4 ~2.4×10 4 , and more preferably 1.2×10 4 ~2.4×10 4 , particularly preferably 1.2×10 4 ~2.3×10 4 It is.

[0029] The high molecular weight component-containing polycarbonate resin (A-1-1 component) can be obtained by mixing the A-1-1-1 and A-1-1-2 components in various ratios and adjusting to satisfy a predetermined molecular weight range. Preferably, the A-1-1-1 component is 2 to 40% by weight, more preferably 3 to 30% by weight, even more preferably 4 to 20% by weight, and particularly preferably 5 to 20% by weight, of 100% by weight of the A-1-1 component.

[0030] Methods for preparing the A-1-1 component include (1) a method in which the A-1-1-1 and A-1-1-2 components are polymerized independently and then mixed; (2) a method in which a polycarbonate resin that shows multiple polymer peaks in a molecular weight distribution chart determined by GPC, as typified by the method shown in JP-A-5-306336, is produced in the same system, and the polycarbonate resin is produced so as to satisfy the conditions of the A-1-1 component of the present invention; and (3) a method in which the polycarbonate resin obtained by the above production method (production method (2)) is mixed with the A-1-1-1 and / or A-1-1-2 components produced separately.

[0031] The viscosity average molecular weight in the present invention is calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and calculate the viscosity average molecular weight M using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7

[0032] The viscosity average molecular weight of the polycarbonate resin in the flame-retardant polycarbonate resin composition of the present invention is calculated as follows. That is, the composition is mixed with methylene chloride in an amount 20 to 30 times by weight, and the soluble components in the composition are dissolved. The soluble components are collected by filtration through Celite. The solvent in the resulting solution is then removed. The solid obtained after the solvent removal is thoroughly dried to obtain a solid of components that are soluble in methylene chloride. 0.7 g of the solid is mixed with methylene chloride. The specific viscosity at 20° C. is determined from a 100 ml solution in the same manner as above, and the viscosity average molecular weight M is calculated from the specific viscosity in the same manner as above.

[0033] A polycarbonate-polydiorganosiloxane copolymer resin can also be used as the polycarbonate resin (component A) of the present invention. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).

[0034] [ka]

[0035] [In the above general formula (1), R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):

[0036] [ka]

[0037] [In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.

[0038] [ka]

[0039] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.]

[0040] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2- Bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'- Dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.

[0041] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.

[0042] As the hydroxyaryl-terminated polydiorganosiloxane represented by the above general formula (3), for example, the compounds shown below are suitably used.

[0043] [ka]

[0044] Hydroxyaryl-terminated polydiorganosiloxane (II) is easily produced by hydrosilylation reaction of phenols having an olefinic unsaturated carbon-carbon bond, preferably vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol, with the end of a polysiloxane chain having a predetermined degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. The molecular weight distribution (Mw / Mn) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 3 or less. In order to achieve even better low outgassing properties during high-temperature molding and low-temperature impact properties, the molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and even more preferably 2 or less. If the upper limit of this preferred range is exceeded, the amount of outgassing during high-temperature molding will be large, and low-temperature impact resistance may be poor.

[0045] Furthermore, in order to achieve a high level of impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is suitably 10 to 300. The diorganosiloxane polymerization degree (p+q) is preferably 10 to 200, more preferably 12 to 150, and even more preferably 14 to 100. Below the lower limit of this preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer is not effectively exhibited, while above the upper limit of this preferred range, poor appearance appears.

[0046] The polydiorganosiloxane content in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.1 to 50% by weight. The polydiorganosiloxane content is more preferably 0.5 to 30% by weight, and even more preferably 1 to 20% by weight. At or above the lower limit of this preferred range, excellent impact resistance and flame retardancy are obtained, while at or below the upper limit of this preferred range, a stable appearance that is not easily affected by molding conditions is easily obtained. The polydiorganosiloxane polymerization degree and polydiorganosiloxane content can be calculated by 1H-NMR measurement.

[0047] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more kinds.

[0048] In addition, as long as it does not interfere with the present invention, other comonomers than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) can be used in an amount of up to 10% by weight based on the total weight of the copolymer.

[0049] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkaline solution.

[0050] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of it may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly advance the polycondensation reaction in the latter stage, and there is no need to add it if it is not necessary.

[0051] The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.

[0052] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing the gaseous compound into the reaction system.

[0053] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture thereof can be used. The proportion of the acid binder used can be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).

[0054] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.

[0055] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and since heat is generated during polymerization in many cases, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be generally specified, but is usually carried out for 0.2 to 10 hours. The pH range for the oligomer formation reaction is the same as that of known interfacial reaction conditions, and the pH is always adjusted to 10 or higher.

[0056] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the mixed solution is stirred while adding hydroxyaryl-terminated polydiorganosiloxane (II) represented by general formula (4) that has been highly refined to a molecular weight distribution (Mw / Mn) of 3 or less to the dihydric phenol (I), and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.

[0057] [ka]

[0058] (In the above general formula (4), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 10 to 300. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0059] In carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. For example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, or mixtures thereof, are used as the acid binder. Specifically, when the hydroxyaryl-terminated polydiorganosiloxane (II) used or a part of the dihydric phenol (I) as described above is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or more of alkali relative to the total mole number of the post-added dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).

[0060] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the above mixture.

[0061] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is in the range of 100 to 0.5 mol, preferably 50 to 2 mol, relative to 100 mol of all dihydric phenol compounds used, and it is naturally possible to use two or more compounds in combination.

[0062] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added.

[0063] The reaction time of such a polymerization reaction is preferably 30 minutes or more, more preferably 50 minutes or more. If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.

[0064] A branching agent can be used in combination with the above dihydric phenol compound to produce a branched polycarbonate-polydiorganosiloxane. Examples of polyfunctional aromatic compounds having three or more functional groups that can be used in such branched polycarbonate-polydiorganosiloxane copolymer resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1 Examples of the hydroxyphenyl ether include trisphenols such as {α,α-dimethylbenzylphenol}-α-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The proportion of the polyfunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol %, more preferably 0.005 to 0.9 mol %, further preferably 0.01 to 0.8 mol %, and particularly preferably 0.05 to 0.4 mol %, based on the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 It can be calculated by H-NMR measurement.

[0065] The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.

[0066] In some cases, the obtained polycarbonate-polydiorganosiloxane copolymer resin is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a polycarbonate-polydiorganosiloxane copolymer resin of formula [1 / c].

[0067] The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer resin of a desired purity (degree of purification).

[0068] The average size of the polydiorganosiloxane domains in the polycarbonate-polydiorganosiloxane copolymer resin molded article is preferably in the range of 1 to 60 nm. Such an average size is more preferably 3 to 55 nm, and even more preferably 5 to 50 nm. If it is below the lower limit of this preferred range, impact resistance and flame retardancy may not be sufficiently exhibited, and if it exceeds the upper limit of this preferred range, impact resistance may not be stably exhibited.

[0069] (Component B: impact modifier) The flame-retardant polycarbonate resin composition of the present invention contains an impact modifier as component B. The impact modifier is selected from the group consisting of butadiene rubber, acrylic rubber, and silicone-acrylic composite rubber. It is preferably a graft polymer obtained by graft polymerizing at least one compound including a (meth)acrylic acid ester compound to one rubber selected from the group consisting of, and more preferably a graft polymer having a core-shell structure. The core-shell type graft polymer is a graft copolymer obtained by copolymerizing a rubber component having a glass transition temperature of 10°C or less as a core with one or more monomers selected from (meth)acrylic acid ester compounds, aromatic alkenyl compounds, and vinyl compounds copolymerizable therewith as a shell.

[0070] Examples of the rubber component of component B include butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, silicone-acrylic composite rubber, isobutylene-silicone composite rubber, isoprene rubber, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, nitrile rubber, ethylene-acrylic rubber, silicone rubber, epichlorohydrin rubber, fluororubber, and those with hydrogen added to the unsaturated bond portion. However, from the viewpoint of the concern of the generation of harmful substances during combustion, rubber components that do not contain halogen atoms are preferable in terms of environmental load. In addition, the glass transition temperature of the rubber component is preferably -10°C or lower, more preferably -30°C or lower, and from these points of view, butadiene rubber and acrylic silicone-acrylic composite rubber are particularly preferable as the rubber component. Composite rubber refers to rubber obtained by copolymerizing two types of rubber components, or rubber polymerized to have an IPN structure in which the components are intertwined with each other so that they cannot be separated. In the core-shell type graft polymer, the particle diameter of the core is preferably 240 to 300 nm, more preferably 250 to 290 nm, and even more preferably 260 to 280 nm, in terms of weight average particle diameter. If the particle diameter is in the range of 240 to 300 nm, better impact resistance may be achieved. In addition, the particle diameter distribution is preferably a bidisperse type having two peaks, and particularly preferably a bidisperse type having two peaks near 100 nm and 300 nm, and may achieve better impact resistance than a monodisperse type having a single peak.

[0071] Examples of aromatic vinyl in the vinyl compound copolymerized as the shell of the core-shell type graft polymer with the rubber component include styrene, α-methylstyrene, p-methylstyrene, alkoxystyrene, and halogenated styrene. Examples of acrylic acid esters include methyl acrylate, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, and octyl acrylate. Examples of methacrylic acid esters include methyl methacrylate, ethyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, and octyl methacrylate, with methyl methacrylate being particularly preferred. Among these, it is particularly preferred to contain methacrylic acid esters such as methyl methacrylate as an essential component, and from the viewpoint of mechanical properties and flame retardancy, it is even more preferred not to contain an aromatic vinyl component. This is because the core-shell type graft polymer has excellent affinity with the polycarbonate resin, so that more rubber components are present in the resin, and the good impact resistance of the polycarbonate resin is more effectively exerted, resulting in good impact resistance of the resin composition. More specifically, the methacrylic acid ester is preferably contained in an amount of 10% by weight or more, more preferably 15% by weight or more, based on 100% by weight of the graft component (100% by weight of the shell in the case of a core-shell polymer). The elastic polymer containing a rubber component having a glass transition temperature of 10° C. or less may be produced by any of the polymerization methods of bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, and the copolymerization method may be either one-stage grafting or multi-stage grafting. It may also be a mixture with a copolymer of only the graft component that is a by-product during production. Furthermore, examples of the polymerization method include a general emulsion polymerization method, a soap-free polymerization method using an initiator such as potassium persulfate, a seed polymerization method, and a two-stage swelling polymerization method. Also, in the suspension polymerization method, a method in which the aqueous phase and the monomer phase are kept separately and both are accurately fed to a continuous disperser, and the particle size is controlled by the rotation speed of the disperser, and a method in which the particle size is controlled in a continuous production method by feeding the monomer phase into an aqueous liquid having dispersibility through a fine orifice or porous filter having a diameter of several to several tens of μm, may be used.In the case of a core-shell type graft polymer, the reaction may be one-stage or multi-stage for both the core and the shell.

[0072] Such polymers are commercially available and can be easily obtained. For example, the rubber component is mainly made of butadiene rubber, and examples thereof include the Metablen E series manufactured by Mitsubishi Chemical Corporation (for example, E-875A, the shell component of which is mainly made of methyl methacrylate, and E-870A, the shell component of which is mainly made of methyl methacrylate and styrene). The rubber component is mainly made of acrylic rubber, and examples thereof include the W series manufactured by Mitsubishi Chemical Corporation (for example, W-600A, the shell component of which is mainly made of methyl methacrylate). The rubber component is mainly made of silicone-acrylic composite rubber, and examples thereof include the Metablen S series manufactured by Mitsubishi Chemical Corporation (for example, S-2001, S-2030, the shell component of which is mainly made of methyl methacrylate).

[0073] The content of component B is 1 to 8 parts by weight, preferably 1.5 to 7 parts by weight, and more preferably 2 to 6 parts by weight, relative to 100 parts by weight of component A. If the content of component B is less than 1 part by weight, sufficient impact strength cannot be obtained, and if it exceeds 8 parts by weight, flame retardancy decreases.

[0074] (Component C: phosphazene) The flame-retardant polycarbonate resin composition of the present invention contains a phosphazene containing 98.5 mol % or more of a phosphazene cyclic trimer as a C component. Such a phosphazene can impart an effect of suppressing the decrease in impact strength and flame retardancy to the flame-retardant polycarbonate resin composition by containing a phosphorus atom and a nitrogen atom in the molecule. When a compound other than phosphazene, such as a phosphorus ester or a condensed phosphorus ester, is used as a phosphorus-based flame retardant, the addition of the compound to a polycarbonate resin causes a decrease in impact strength and flame retardancy, and further causes a decrease in impact strength and flame retardancy due to moist heat deterioration. The phosphazene is not particularly limited as long as it does not contain a halogen atom and has a phosphazene structure in the molecule. The phosphazene structure here refers to a structure represented by the formula: -P(R2)=N- [wherein R2 is an organic group]. The phosphazene is represented by the general formulas (5) and (6).

[0075] [ka]

[0076] [ka]

[0077] (In the formula, X1, X2, X3, and X4 represent hydrogen, a hydroxyl group, an amino group, or an organic group not containing a halogen atom, and n represents an integer of 3 to 10.)

[0078] In the above formulas (5) and (6), the halogen atoms represented by X1, X2, X3, and X4 are not included. Examples of the organic group include an alkoxy group, a phenyl group, an amino group, and an allyl group.

[0079] The phosphazene component C must contain 98.5 mol% or more of a phosphazene cyclic trimer. The content is preferably 99 mol% to 100 mol%, more preferably 99.5 mol% to 100 mol%. If the content of the phosphazene cyclic trimer is less than 98.5 mol%, the decrease in impact strength and flame retardancy due to wet heat deterioration cannot be suppressed.

[0080] General methods for producing phosphazenes are described in European Patent Application Publication No. 728811 and International Patent Publication No. WO 97 / 40092, among others.

[0081] During the production process, phosphazene produces cyclic trimers and higher oligomers as by-products in addition to the cyclic trimers. However, the content of the phosphazene cyclic trimers can be increased by purifying the product using column chromatography or other methods.

[0082] The content of the phosphazene cyclic trimer in the phosphazene is 31 It can be quantified by PNMR (chemical shifts: delta trimer 6.5 to 10.0 ppm, delta tetramer -10 to -13.5 ppm, higher oligomers -16.5 to -25.0 ppm).

[0083] The content of component C is 1 to 8 parts by weight, preferably 1.5 to 7 parts by weight, and more preferably 2 to 6 parts by weight, per 100 parts by weight of component A. If the content of component C is less than 1 part by weight, the flame retardant effect cannot be obtained, and if it exceeds 8 parts by weight, the impact strength decreases.

[0084] (Component D: organic sulfonic acid metal salt) The flame-retardant polycarbonate resin composition of the present invention contains an organic sulfonate metal salt as component D. When component D is a flame retardant other than an organic sulfonate metal salt, not only is a sufficient flame retardant effect not obtained, but also the decrease in flame retardancy and impact strength due to wet heat deterioration is not suppressed. The organic sulfonate metal salt is preferably an organic sulfonate alkali (earth) metal salt having 1 to 50, preferably 1 to 40, carbon atoms. The organic sulfonate alkali (earth) metal salt includes a metal salt of a fluorine-substituted alkylsulfonic acid such as a metal salt of a perfluoroalkylsulfonic acid having 1 to 10, preferably 2 to 8, carbon atoms and an alkali metal or alkaline earth metal, and a metal salt of an aromatic sulfonic acid having 7 to 50, preferably 7 to 40, carbon atoms and an alkali metal or alkaline earth metal. Examples of the alkali metal constituting the metal salt include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. An alkali metal is more preferable. Among these alkali metals, rubidium and cesium, which have a larger ionic radius, are suitable when transparency is required, but they are not widely used and are difficult to purify, which may result in a disadvantage in terms of cost. On the other hand, metals with a smaller ionic radius, such as lithium and sodium, may be disadvantageous in terms of flame retardancy. Taking these factors into consideration, the alkali metals in the alkali metal sulfonates can be used differently, but potassium sulfonates, which have an excellent balance of properties, are most suitable in all respects. Such potassium salts can also be used in combination with alkali metal sulfonates made of other alkali metals.

[0085] Specific examples of the alkali metal salt of perfluoroalkylsulfonate include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctane sulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctane sulfonate, lithium trifluoromethanesulfonate, and perfluorobutanesulfonate. Examples of the perfluoroalkyl sulfonate include lithium sulfonate, lithium perfluoroheptanesulfonate, cesium trifluoromethanesulfonate, cesium perfluorobutanesulfonate, cesium perfluorooctane sulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate. These can be used alone or in combination of two or more. The number of carbon atoms in the perfluoroalkyl group is preferably in the range of 1 to 18, more preferably in the range of 1 to 10, and even more preferably in the range of 1 to 8. Among these, potassium perfluorobutanesulfonate is particularly preferred. In perfluoroalkylsulfonic acid alkali (earth) metal salts made of alkali metals, fluoride ions (F-) are usually mixed in no small amount. The presence of such fluoride ions can be a factor in reducing flame retardancy, so it is preferable to reduce them as much as possible. The proportion of such fluoride ions can be measured by ion chromatography. The content of fluoride ions is preferably 100 ppm or less, more preferably 40 ppm or less, and particularly preferably 10 ppm or less. For production efficiency, it is preferable that the content is 0.2 ppm or more. The perfluoroalkylsulfonic acid alkali (earth) metal salt with reduced fluoride ion content can be produced by a known production method, and by a method of reducing the amount of fluoride ions contained in the raw material when producing a fluorine-containing organic metal salt, a method of removing hydrogen fluoride obtained by the reaction by gas generated during the reaction or by heating, and a method of reducing the amount of fluoride ions by using a purification method such as recrystallization and reprecipitation when producing a fluorine-containing organic metal salt. In particular, since organic sulfonic acid metal salts are relatively soluble in water, it is preferable to use ion-exchanged water, particularly water with an electric resistance value of 18 MΩ·cm or more, that is, an electric conductivity of about 0.55 μS / cm or less, and dissolve and wash at a temperature higher than room temperature, and then cool and recrystallize.Specific examples of the aromatic sulfonic acid alkali (earth) metal salts include disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium 5-sulfoisophthalate, sodium 5-sulfoisophthalate, polysodium polyethylene terephthalate polysulfonate, calcium 1-methoxynaphthalene-4-sulfonate, disodium 4-dodecylphenyl ether disulfonate, polysodium poly(2,6-dimethylphenylene oxide) polysulfonate, polysodium poly(1,3-phenylene oxide) polysulfonate, polysodium poly(1,4-phenylene oxide) polysulfonate, polypotassium poly(2,6-diphenylphenylene oxide) polysulfonate, lithium poly(2-fluoro-6-butylphenylene oxide) polysulfonate, potassium sulfonate of benzenesulfonate, sodium benzenesulfonate, and benzenesulfonic acid. Examples of the sulfonate include strontium, magnesium benzenesulfonate, dipotassium p-benzenedisulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, a formalin condensate of sodium naphthalenesulfonate, and a formalin condensate of sodium anthracenesulfonate. Of these alkali (earth) metal salts of aromatic sulfonic acid, potassium salts are particularly preferred.Among these alkali (earth) metal salts of aromatic sulfonates, potassium diphenylsulfone-3-sulfonate and dipotassium diphenylsulfone-3,3'-disulfonate are preferred, and a mixture thereof (wherein the weight ratio of the former to the latter is 15 / 85 to 30 / 70) is particularly preferred.

[0086] The content of the D component is 0.01 to 0.5 parts by weight, preferably 0.03 to 0.4 parts by weight, and more preferably 0.05 to 0.3 parts by weight, based on 100 parts by weight of the A component. If the content is less than 0.01 part by weight, the decrease in flame retardancy due to moist heat deterioration cannot be suppressed, whereas if it exceeds 0.5 part by weight, the impact strength decreases.

[0087] (E component: Anti-drip agent) The flame-retardant polycarbonate resin composition of the present invention contains an anti-drip agent as component E. By containing this anti-drip agent, good flame retardancy can be achieved without impairing the physical properties of the molded article.

[0088] The drip prevention agent of component E may be a fluorine-containing polymer having fibril-forming ability, and examples of such polymers include polytetrafluoroethylene, tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), partially fluorinated polymers as shown in U.S. Patent No. 4,379,910, polycarbonate resins produced from fluorinated diphenols, etc. Among these, polytetrafluoroethylene (hereinafter sometimes referred to as PTFE) is preferred.

[0089] The molecular weight of the fibril-forming PTFE is extremely high, and it shows a tendency to bond PTFE to each other and become fibrous by external action such as shear force. The molecular weight is 1 million to 10 million, preferably 2 million to 9 million, in terms of number average molecular weight calculated from the standard specific gravity. Such PTFE can be used in the form of a solid or an aqueous dispersion. In addition, such fibril-forming PTFE can be used in the form of a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties.

[0090] Commercially available PTFE products having such fibril-forming ability include, for example, Teflon (registered trademark) 6J from Mitsui DuPont Fluorochemicals Co., Ltd. and Polyflon MPA from Daikin Industries, Ltd. Representative examples of commercially available aqueous dispersions of PTFE include Fluon AD-1 and AD-936 manufactured by Asahi ICI Fluoropolymers Co., Ltd., Fluon D-1 and D-2 manufactured by Daikin Industries, Ltd., and Teflon (registered trademark) 30J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd.

[0091] The mixed form of PTFE can be prepared by (1) mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating to obtain a co-agglomerated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.), (2) mixing an aqueous dispersion of PTFE with dried organic polymer particles (method described in JP-A-4-272957), or (3) homogeneously mixing an aqueous dispersion of PTFE with an organic polymer particle solution and extracting each medium from the mixture at the same time. (4) a method of polymerizing a monomer that forms an organic polymer in an aqueous dispersion of PTFE (method described in JP-A-06-220210, JP-A-08-188653, etc.), and (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (method described in JP-A-11-29679, etc.). Commercially available products of these mixed forms of PTFE include "Metabrene A3800" (trade name) manufactured by Mitsubishi Chemical Corporation and "BLENDEX B449" (trade name) manufactured by GE Specialty Chemicals.

[0092] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, in 100% by weight of the PTFE mixture. When the proportion of PTFE is within this range, good dispersibility of PTFE may be achieved. Note that the proportion of the above F component indicates the net amount of the drip prevention agent, and in the case of the mixed form PTFE, indicates the net amount of PTFE.

[0093] The content of component E is 0.05 to 2 parts by weight, preferably 0.1 to 1.5 parts by weight, and more preferably 0.2 to 1 part by weight, relative to 100 parts by weight of component A. If the content of component E is less than 0.05 parts by weight, sufficient flame retardancy cannot be obtained, and if it exceeds 2 parts by weight, impact strength decreases.

[0094] In addition, examples of the styrene monomer used in the organic polymer used in the polytetrafluoroethylene blend of the present invention include styrenes that may be substituted with one or more groups selected from the group consisting of alkyl groups having 1 to 6 carbon atoms, alkoxy groups having 1 to 6 carbon atoms, and halogens, such as ortho-methylstyrene, meta-methylstyrene, para-methylstyrene, dimethylstyrene, ethyl-styrene, para-tert-butylstyrene, methoxystyrene, fluorostyrene, monobromostyrene, dibromostyrene, and tribromostyrene, vinylxylene, and vinylnaphthalene, but are not limited thereto. The styrene monomers can be used alone or in combination of two or more types.

[0095] The acrylic monomer used in the organic polymer used in the polytetrafluoroethylene blend of the present invention includes a (meth)acrylate derivative which may be substituted. Specifically, the acrylic monomer is a (meth)acrylate derivative which may be substituted with one or more groups selected from the group consisting of an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group, and a glycidyl group, such as (meth)acrylonitrile, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, hexyl (meth)acrylate, 2-ethyl ... Examples of the acrylic monomer include, but are not limited to, (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate and glycidyl (meth)acrylate, maleimides which may be substituted with an alkyl group having 1 to 6 carbon atoms or an aryl group, such as maleimide, N-methyl-maleimide and N-phenyl-maleimide, maleic acid, phthalic acid and itaconic acid. The acrylic monomer may be used alone or in a mixture of two or more kinds. Among these, (meth)acrylonitrile is preferred.

[0096] The amount of the acrylic monomer-derived units contained in the organic polymer used in the coating layer is preferably 8 to 11 parts by weight, more preferably 8 to 10 parts by weight, and even more preferably 8 to 9 parts by weight, based on 100 parts by weight of the styrene monomer-derived units. If the amount of the acrylic monomer-derived units is less than 8 parts by weight, the coating strength may decrease, and if it is more than 11 parts by weight, the surface appearance of the molded article may deteriorate.

[0097] The polytetrafluoroethylene mixture of the present invention preferably has a residual moisture content of 0.5% by weight or less, more preferably 0.2 to 0.4% by weight, and even more preferably 0.1 to 0.3% by weight. If the residual moisture content is more than 0.5% by weight, it may adversely affect the flame retardancy.

[0098] The process for producing the polytetrafluoroethylene blend of the present invention includes a step of forming a coating layer containing one or more monomers selected from the group consisting of styrene monomers and acrylic monomers on the outside of the branched polytetrafluoroethylene in the presence of an initiator. Furthermore, it is preferable to include a step of drying after the step of forming the coating layer so that the residual moisture content is 0.5% by weight or less, preferably 0.2 to 0.4% by weight, more preferably 0.1 to 0.3% by weight. The drying step can be performed using a method known in the art, such as hot air drying or vacuum drying.

[0099] The initiator used in the polytetrafluoroethylene mixture of the present invention may be any initiator used in the polymerization reaction of styrene-based and / or acrylic monomers without limitation. Examples of the initiator include, but are not limited to, cumyl hydroperoxide, di-tert-butyl peroxide, benzoyl peroxide, hydrogen peroxide, and potassium peroxide. In the polytetrafluoroethylene mixture of the present invention, one or more of the initiators may be used depending on the reaction conditions. The amount of the initiator is freely selected within the range used in consideration of the amount of polytetrafluoroethylene and the type / amount of monomer, and is preferably used in an amount of 0.15 to 0.25 parts by weight based on the amount of the total composition.

[0100] The polytetrafluoroethylene mixture of the present invention was produced by the suspension polymerization method according to the following procedure.

[0101] First, water and a branched polytetrafluoroethylene dispersion (solid concentration: 60%, polytetrafluoroethylene particle size: 0.15 to 0.3 μm) were placed in a reactor, and then acrylic monomer, styrene monomer, and cumene hydroperoxide as a water-soluble initiator were added while stirring, and the reaction was carried out at 80 to 90°C for 9 hours. After the reaction was completed, the water was removed by centrifugation for 30 minutes in a centrifuge, and a paste-like product was obtained. The paste product was then dried in a hot air dryer at 80 to 100°C for 8 hours. The dried product was then pulverized to obtain a polytetrafluoroethylene-based mixture of the present invention.

[0102] Such suspension polymerization does not require a polymerization step by emulsion dispersion in the emulsion polymerization method exemplified in Patent No. 3469391, and does not require an emulsifier and electrolyte salts for coagulating and precipitating the latex after polymerization. In addition, in the polytetrafluoroethylene mixture produced by the emulsion polymerization method, the emulsifier and electrolyte salts in the mixture tend to be mixed and are difficult to remove, so it is difficult to reduce the sodium metal ions and potassium metal ions derived from the emulsifier and electrolyte salts. Since the polytetrafluoroethylene mixture used in the present invention is produced by the suspension polymerization method, it does not use the emulsifier and electrolyte salts, so that the sodium metal ions and potassium metal ions in the mixture can be reduced, and the thermal stability and hydrolysis resistance can be improved.

[0103] In addition, in the present invention, coated branched PTFE can be used as the drip prevention agent. The coated branched PTFE is a polytetrafluoroethylene mixture consisting of branched polytetrafluoroethylene particles and an organic polymer, and has a coating layer consisting of an organic polymer, preferably a polymer containing a unit derived from a styrene monomer and / or a unit derived from an acrylic monomer, on the outside of the branched polytetrafluoroethylene. The coating layer is formed on the surface of the branched polytetrafluoroethylene. In addition, the coating layer preferably contains a copolymer of a styrene monomer and an acrylic monomer.

[0104] The polytetrafluoroethylene contained in the coated branched PTFE is branched polytetrafluoroethylene. If the polytetrafluoroethylene contained is not branched polytetrafluoroethylene, the drip prevention effect will be insufficient when the amount of polytetrafluoroethylene added is small. The branched polytetrafluoroethylene is particulate and has a particle size of preferably 0.1 to 0.6 μm, more preferably 0.3 to 0.5 μm, and even more preferably 0.3 to 0.4 μm. If the particle size is smaller than 0.1 μm, the surface appearance of the molded product is excellent, but it is difficult to commercially obtain polytetrafluoroethylene having a particle size smaller than 0.1 μm. Also, if the particle size is larger than 0.6 μm, the surface appearance of the molded product may deteriorate. The number average molecular weight of the polytetrafluoroethylene used in the present invention is 1×10 4 ~1×10 7 is preferable, and more preferably 2×10 6 ~9×10 6 Generally, polytetrafluoroethylene with a high molecular weight is more preferable in terms of stability. Either powder or dispersion form can be used. The content of branched polytetrafluoroethylene in the coated branched PTFE is preferably 20 to 60 parts by weight, more preferably 40 to 55 parts by weight, further preferably 47 to 53 parts by weight, particularly preferably 48 to 52 parts by weight, and most preferably 49 to 51 parts by weight, based on 100 parts by weight of the total weight of the coated branched PTFE. When the proportion of branched polytetrafluoroethylene is within this range, good dispersibility of the branched polytetrafluoroethylene may be achieved.

[0105] (Other additives) (i) Phosphorus-based stabilizers Examples of phosphorus-based stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines.

[0106] Specific examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, tris(diethylphenyl)phosphite, tris(di-iso-propylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, and dicyclohexyl pentaerythritol diphosphite.

[0107] Other phosphite compounds that react with dihydric phenols to form a cyclic structure can also be used, such as 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite.

[0108] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate.

[0109] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, and tetrakis (2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis(2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl) Examples of the phosphonite include tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite, and more preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups.

[0110] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0111] Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine.

[0112] The phosphorus-based stabilizer may be used alone or in combination of two or more. Among the phosphorus-based stabilizers, a phosphonite compound or a phosphite compound represented by the following general formula (7) is preferred.

[0113] [ka]

[0114] (In formula (7), R and R' represent an alkyl group having 6 to 30 carbon atoms or an aryl group having 6 to 30 carbon atoms, and may be the same or different.)

[0115] As described above, the phosphonite compound is preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite, and stabilizers containing this phosphonite as a main component are commercially available as Sandostab P-EPQ (trademark, manufactured by Clariant) and Irgafos P-EPQ (trademark, manufactured by CIBA SPECIALTY CHEMICALS), either of which can be used.

[0116] Among the above formula (7), more preferred phosphite compounds are distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite.

[0117] Distearyl pentaerythritol diphosphite is commercially available as ADK STAB PEP-8 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and JPP681S (trademark, manufactured by Johoku Chemical Industry Co., Ltd.), and any of these can be used. Bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-24G (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.), Alkanox P-24 (trademark, manufactured by Great Lakes), Ultranox P626 (trademark, manufactured by GE Specialty Chemicals), Doverphos S-9432 (trademark, manufactured by Dover Chemical), and Irgaofos 126 and 126FF (trademarks, manufactured by CIBA SPECIALTY CHEMICALS), and any of these can be used. Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-36 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and can be easily used. Bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite is commercially available as ADK STAB PEP-45 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and Doverphos S-9228 (trademark, manufactured by Dover Chemical Co., Ltd.), and either can be used.

[0118] The phosphorus-based stabilizers can be used alone or in combination of two or more kinds. The content of the phosphorus-based stabilizer is preferably 0.01 to 1.0 parts by weight, more preferably 0.03 to 0.8 parts by weight, and even more preferably 0.05 to 0.5 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.01 part by weight, the effect of suppressing thermal decomposition during processing may not be exhibited, and mechanical properties may not deteriorate, while if the content exceeds 1.0 part by weight, mechanical properties may deteriorate.

[0119] (ii) Phenolic stabilizers The resin composition of the present invention may contain a phenol-based stabilizer. Examples of phenol-based stabilizers include hindered phenols, semi-hindered phenols, and less hindered phenol compounds. From the viewpoint of providing a heat stabilizing formulation to a polypropylene resin, a hindered phenol compound is more preferably used. Examples of such hindered phenol compounds include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, and the like. , 3,5-di-tert-butyl-4-hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-p-benzyl- cresol), 2,2'-ethylidene-bis(4,6-di-tert-butylphenol), 2,2'-butylidene-bis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-di-thiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy- 3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylenebis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydrazine hydroxyphenyl) isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, 1,3,5-tris2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert -butyl-4-hydroxy-5-methylphenyl)propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetate, 3,9-bis[2-{3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,Examples include 6-tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate. Among the above compounds, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferably used, and further, (3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol represented by the following formula (8) and 1,3,5-tris-(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione represented by the following formula (9) are more preferably used as they are excellent in suppressing deterioration of mechanical properties due to thermal decomposition during processing.

[0120] [ka]

[0121] [ka]

[0122] The above phenol-based stabilizers can be used alone or in combination of two or more. The content of the phenol-based stabilizer is preferably 0.05 to 1.0 parts by weight, more preferably 0.07 to 0.8 parts by weight, and even more preferably 0.1 to 0.5 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.05 parts by weight, the effect of suppressing thermal decomposition during processing may not be exhibited, and mechanical properties may decrease, while if the content exceeds 1.0 part by weight, mechanical properties may decrease.

[0123] It is preferable to use either a phosphorus-based stabilizer or a phenol-based stabilizer, and more preferable to use them in combination. When using them in combination, it is preferable to use 0.01 to 0.5 parts by weight of a phosphorus-based stabilizer and 0.01 to 0.5 parts by weight of a phenol-based stabilizer per 100 parts by weight of component A.

[0124] (iii) Ultraviolet absorber The flame-retardant polycarbonate resin composition of the present invention may contain an ultraviolet absorber. Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxytrihydridolate benzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodium sulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.

[0125] Benzotriazoles include, for example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the polymer include polymers having a 2-hydroxyphenyl-2H-benzotriazole skeleton, such as azole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, as well as copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.

[0126] Examples of hydroxyphenyl triazines include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is replaced with a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol.

[0127] Examples of cyclic imino esters include 2,2'-p-phenylenebis(3,1-benzoxazin-4-one), 2,2'-m-phenylenebis(3,1-benzoxazin-4-one), and 2,2'-p,p'-diphenylenebis(3,1-benzoxazin-4-one).

[0128] Examples of cyanoacrylates include 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene.

[0129] Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.

[0130] Among the above compounds, in the present invention, a compound represented by any one of the following formulas (10), (11) and (12) is more preferably used.

[0131] [ka]

[0132] [ka]

[0133] [ka]

[0134] The above ultraviolet absorbents can be used alone or in combination of two or more kinds. The content of the ultraviolet absorber is preferably 0.1 to 3 parts by weight, more preferably 0.12 to 2 parts by weight, and further preferably 0.15 to 1 part by weight, relative to 100 parts by weight of component A. If the content of the ultraviolet absorber is less than 0.1 part by weight, sufficient light resistance may not be exhibited, while if it is more than 3 parts by weight, it is not preferable in terms of poor appearance and deterioration of physical properties due to gas generation.

[0135] (iv) Hindered amine light stabilizers The flame-retardant polycarbonate resin composition of the present invention may contain a hindered amine light stabilizer. Hindered amine light stabilizers are generally called HALS (Hindered Amine Light Stabilizers), and are compounds having a 2,2,6,6-tetramethylpiperidine skeleton in their structure, such as 4-acetoxy-2,2,6,6-tetramethylpiperidine, 4-stearoyloxy-2,2,6,6-tetramethylpiperidine, 4-acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(phenylacetoxy)-2,2,6,6-tetramethylpiperidine, 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-methoxy-2,2, 6,6-Tetramethylpiperidine, 4-Stearyloxy-2,2,6,6-tetramethylpiperidine, 4-Cyclohexyloxy-2,2,6,6-tetramethylpiperidine, 4-Benzyloxy-2,2,6,6-tetramethylpiperidine, 4-Phenoxy-2,2,6,6-tetramethylpiperidine, 4-(Ethylcarbamoyloxy)-2,2,6,6-tetramethylpiperidine, 4-(Cyclohexylcarbamoyloxy)-2,2,6,6-tetramethylpiperidine, 4-(Phenylcarbamoyloxy)-2,2,6,6-tetramethylpiperidine rubamoyloxy)-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl)carbonate, bis(2,2,6,6-tetramethyl-4-piperidyl)oxalate, bis(2,2,6,6-tetramethyl-4-piperidyl)malonate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl)adipate, bis(2,2,6,6-tetramethyl-4-piperidyl)terephthalate , bis(1,2,2,6,6-pentamethyl-4-piperidyl)carbonate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)oxalate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)malonate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)adipate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)terephthalate, N,N'-bis-2,2,6,6-Tetramethyl-4-piperidinyl-1,3-benzenedicarboxamide, 1,2-bis(2,2,6,6-tetramethyl-4-piperidyloxy)ethane, α,α'-bis(2,2,6,6-tetramethyl-4-piperidyloxy)-p-xylene, bis(2,2,6,6-tetramethyl-4-piperidyltolylene-2,4-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidyl)-hexamethylene-1,6-dicarbamate, tris(2,2,6,6-tetramethyl-4-piperidyl)-benzene-1,3, 5-tricarboxylate, N,N',N'',N'''-tetrakis-(4,6-bis-(butyl-(N-methyl-2,2,6,6-tetramethylpiperidin-4-yl)amino)-triazin-2-yl)-4,7-diazadecane-1,10-diamine, polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, poly[{6-(1,1,3,3-tetramethyl (2,2,6,6-tetramethyl-4-piperidyl)imino)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, tris(2,2,6,6-tetramethyl-4-piperidyl)-benzene-1,3, 4-tricarboxylate, 1-[2-{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy}butyl]-4-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy]2,2,6,6-tetramethylpiperidine, and a condensation product of 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol, and β,β,β',β'-tetramethyl-3,9-[2,4,8,10-tetraoxaspiro(5,5)undecane]diethanol.

[0136] Hindered amine light stabilizers are broadly divided into three types based on the bonding partner of the nitrogen atom in the piperidine skeleton: NH type (hydrogen bonded to the nitrogen atom), NR type (alkyl group (R) bonded to the nitrogen atom), and N-OR type (alkoxy group (OR) bonded to the nitrogen atom). From the viewpoint of the basicity of the hindered amine light stabilizer, it is more preferable to use the NR type or N-OR type, which have low basicity, when applying it to polycarbonate resin.

[0137] Among the above compounds, the compounds represented by the following formulae (13) and (14) are more preferably used in the present invention.

[0138] [ka]

[0139] [ka]

[0140] The hindered amine light stabilizer can be used alone or in combination of two or more kinds. The content of the hindered amine light stabilizer is preferably 0 to 1 part by weight, more preferably 0.05 to 1 part by weight, further preferably 0.08 to 0.7 parts by weight, and particularly preferably 0.1 to 0.5 parts by weight, relative to 100 parts by weight of the A component. If the content of the hindered amine light stabilizer is more than 1 part by weight, there may be cases where poor appearance due to gas generation or physical properties are reduced due to decomposition of the polycarbonate resin. If the content is less than 0.05 parts by weight, there may be cases where sufficient light resistance is not exhibited.

[0141] (v) Release agent It is preferable to further blend a mold release agent in the flame-retardant polycarbonate resin composition of the present invention for the purpose of improving the productivity during molding and reducing distortion of the molded product. As such a mold release agent, a known one can be used. For example, saturated fatty acid ester, unsaturated fatty acid ester, polyolefin wax (polyethylene wax, 1-alkene polymer, etc., those modified with a functional group-containing compound such as acid modification can also be used), silicone compound, fluorine compound (fluorine oil represented by polyfluoroalkyl ether, etc.), paraffin wax, beeswax, etc. can be mentioned. Among them, fatty acid ester can be mentioned as a preferable mold release agent. Such fatty acid ester is an ester of an aliphatic alcohol and an aliphatic carboxylic acid. Such aliphatic alcohol may be a monohydric alcohol or a polyhydric alcohol having dihydric or more. The carbon number of the alcohol is in the range of 3 to 32, more preferably in the range of 5 to 30. As such a monohydric alcohol, for example, dodecanol, tetradecanol, hexadecanol, octadecanol, eicosanol, tetracosanol, ceryl alcohol, and triacontanol can be exemplified. Examples of such polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, polyglycerol (triglycerol to hexaglycerol), ditrimethylolpropane, xylitol, sorbitol, and mannitol. In the fatty acid ester of the present invention, polyhydric alcohols are more preferred.

[0142] On the other hand, the aliphatic carboxylic acid preferably has 3 to 32 carbon atoms, and particularly preferably has 10 to 22 carbon atoms. Examples of the aliphatic carboxylic acid include saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, behenic acid, icosanoic acid, and docosanoic acid, and unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid, and cetoleic acid. Among the above, the aliphatic carboxylic acid is preferably one having 14 to 20 carbon atoms. Among them, saturated aliphatic carboxylic acids are preferred. Stearic acid and palmitic acid are particularly preferred.

[0143] The above-mentioned aliphatic carboxylic acids such as stearic acid and palmitic acid are usually produced from natural oils and fats such as animal oils and fats such as beef tallow and lard, and vegetable oils and fats such as palm oil and sunflower oil. Therefore, these aliphatic carboxylic acids are usually produced from other oils and fats with different numbers of carbon atoms. Therefore, in the production of the fatty acid ester of the present invention, aliphatic carboxylic acids, particularly stearic acid and palmitic acid, which are produced from such natural fats and oils and are in the form of a mixture containing other carboxylic acid components, are preferably used.

[0144] The fatty acid ester of the present invention may be either a partial ester or a full ester (full ester). However, partial esters usually have a high hydroxyl value and tend to induce decomposition of the resin at high temperatures, so full esters are more preferred. The acid value of the fatty acid ester of the present invention is preferably 20 or less, more preferably in the range of 4 to 20, and even more preferably in the range of 4 to 12, from the viewpoint of thermal stability. The acid value can be substantially 0. The hydroxyl value of the fatty acid ester is more preferably in the range of 0.1 to 30. The iodine value is preferably 10 or less. The iodine value can be substantially 0. These properties can be determined by the method specified in JIS K 0070.

[0145] The content of the mold release agent is preferably 0.005 to 2 parts by weight, more preferably 0.01 to 1 part by weight, and even more preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of the A component. In this range, the flame-retardant polycarbonate resin composition may have good mold releasability and roll releasability. In particular, such an amount of fatty acid ester may provide a flame-retardant polycarbonate resin composition having good mold releasability and roll releasability without impairing a good hue.

[0146] (vi) Dyes and pigments The flame-retardant polycarbonate resin composition of the present invention can further contain various dyes and pigments to provide molded products with a variety of designs. By blending a fluorescent brightening agent or other fluorescent dye that emits light, it is possible to impart a better design effect by making use of the emitted color. It is also possible to provide a flame-retardant polycarbonate resin composition that is colored with a very small amount of dyes and pigments and has vivid color development.

[0147] Examples of the fluorescent dyes (including fluorescent whitening agents) used in the present invention include coumarin-based fluorescent dyes, benzopyran-based fluorescent dyes, perylene-based fluorescent dyes, anthraquinone-based fluorescent dyes, thioindigo-based fluorescent dyes, xanthene-based fluorescent dyes, xanthone-based fluorescent dyes, thioxanthene-based fluorescent dyes, thioxanthone-based fluorescent dyes, thiazine-based fluorescent dyes, and diaminostilbene-based fluorescent dyes. Among these, coumarin-based fluorescent dyes, benzopyran-based fluorescent dyes, and perylene-based fluorescent dyes are preferred because they have good heat resistance and are less likely to deteriorate during molding of polycarbonate resin.

[0148] Examples of dyes other than the above bluing agents and fluorescent dyes include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. As the metallic pigment, those having a metal coating or a metal oxide coating on various plate-like fillers are suitable.

[0149] The content of the dye or pigment is preferably from 0.00001 to 1 part by weight, and more preferably from 0.00005 to 0.5 parts by weight, per 100 parts by weight of the A component.

[0150] (vii) Other heat stabilizers The flame-retardant polycarbonate resin composition of the present invention may also contain heat stabilizers other than the phosphorus-based stabilizers and phenol-based stabilizers. Such other heat stabilizers are preferably used in combination with either one of these stabilizers or the antioxidant, and particularly preferably in combination with both. It is preferable that the other heat stabilizer is used. Suitable examples of such other heat stabilizers include lactone stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene (details of such stabilizers are described in JP-A-7-233160). Such a compound is commercially available as Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), and this compound can be used. Furthermore, stabilizers in which the compound is mixed with various phosphite compounds and hindered phenol compounds are commercially available. Suitable examples include Irganox HP-2921 manufactured by the above company. Such premixed stabilizers can also be used in the present invention. The amount of lactone stabilizer to be blended is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of component A.

[0151] Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. Such stabilizers are particularly effective when the resin composition is applied to rotational molding. The amount of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of component A.

[0152] (viii) Filling material In the flame-retardant polycarbonate resin composition of the present invention, various fillers can be blended as reinforcing fillers within the range in which the effects of the present invention are exhibited. For example, silicate minerals, calcium carbonate, glass fibers, glass beads, glass balloons, milled glass fibers, glass flakes, carbon fibers, carbon flakes, carbon beads, milled carbon fibers, graphite, vapor-grown ultrafine carbon fibers (fiber diameter less than 0.1 μm), carbon nanotubes (fiber diameter less than 0.1 μm, hollow), fullerenes, metal flakes, metal fibers, metal-coated glass fibers, metal-coated carbon fibers, metal-coated glass flakes, silica, metal oxide particles, metal oxide fibers, metal oxide balloons, and various whiskers (potassium titanate whiskers, aluminum borate whiskers, basic magnesium sulfate, etc.). These reinforcing fillers may be included in one type or in combination of two or more types.

[0153] The content of these fillers is preferably 0.1 to 60 parts by weight, and more preferably 0.5 to 50 parts by weight, based on 100 parts by weight of component A.

[0154] (ix) Other resins and elastomers The resin composition of the present invention may contain small amounts of other resins or elastomers as long as the effects of the present invention are exhibited.

[0155] Examples of such other resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polymethacrylate resins, phenolic resins, and epoxy resins.

[0156] Examples of the elastomer include isobutylene / isoprene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, and polyamide elastomers.

[0157] (x) Other additives In addition, the flame-retardant polycarbonate resin composition of the present invention can be used to impart various functions to molded articles. For the purpose of improving the properties, small amounts of additives known per se can be added. These additives are added in normal amounts so long as they do not impair the object of the present invention.

[0158] Such additives include sliding agents (e.g., PTFE particles), colorants (e.g., pigments such as carbon black and titanium oxide, dyes), light diffusing agents (e.g., acrylic crosslinked particles, silicone crosslinked particles, extremely thin glass flakes, calcium carbonate particles), fluorescent dyes, inorganic phosphors (e.g., phosphors having an aluminate as a host crystal), antistatic agents, crystal nucleating agents, inorganic and organic antibacterial agents, photocatalytic antifouling agents (e.g., fine particle titanium oxide, fine particle zinc oxide), radical generators, infrared absorbing agents (heat ray absorbing agents), and photochromic agents.

[0159] <Method of producing resin composition> Any method can be used to produce the flame-retardant polycarbonate resin composition of the present invention. For example, the components and optionally other components are premixed, then melt-kneaded, and pelletized. Examples of premixing means include a Nauta mixer, a V-type blender, a Henschel mixer, a mechanochemical device, and an extrusion mixer. In premixing, granulation can be performed using an extrusion granulator or a briquetting machine. After premixing, the mixture is melt-kneaded using a melt kneader such as a vented twin-screw extruder, and pelletized using a pelletizer or other device. Other examples of the melt kneader include a Banbury mixer, a kneading roll, and a thermostatic stirring vessel, but a vented twin-screw extruder is preferred. Alternatively, the components and optionally other components can be fed independently to a melt kneader such as a twin-screw extruder without premixing.

[0160] <About the molded body> The flame-retardant polycarbonate resin composition of the present invention obtained as described above can be used to produce various products by injection molding the pellets produced as described above. Furthermore, it is also possible to directly produce sheets, films, irregular extrusion molded products, and injection molded products from the resin melt-kneaded in an extruder without passing through pellets. In such injection molding, molded products can be obtained using injection molding methods such as injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding, in addition to ordinary molding methods, depending on the purpose. The advantages of these various molding methods are already widely known. In addition, molding can be performed using either the cold runner method or the hot runner method. In addition, the resin composition of the present invention can be used to mold various irregular extrusion molded products and sheets by extrusion molding. Effect of the Invention

[0161] The flame-retardant polycarbonate resin composition of the present invention is a resin composition that is excellent in impact strength and flame retardancy and is inhibited from decreasing in impact strength and flame retardancy due to moisture resistance deterioration, and is therefore widely useful in the fields of office automation equipment, electronic and electrical equipment, and various other fields. Therefore, the industrial effects of the present invention are extremely great. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0162] The embodiments of the present invention are those that summarize the preferred ranges of the above-mentioned requirements, and representative examples are described in the following examples. However, the present invention is not limited to these embodiments. EXAMPLES

[0163] The present invention will be further described below with reference to examples. In the examples, parts are by weight and % is by weight unless otherwise specified. Evaluations were performed by the following methods.

[0164] (Evaluation of flame-retardant polycarbonate resin compositions) (i) Charpy impact strength Using the ISO bending test pieces obtained by the method described below, the notched Charpy impact strength was measured according to ISO 179. (ii) Flame retardancy Using the UL test specimens obtained by the method described below, V tests were carried out in accordance with UL 94. Note that cases where the judgment did not meet the criteria of V-0, V-1, or V-2 were indicated as "not V." (iii) Moisture and heat resistance The notched Charpy impact strength and flame retardancy after the wet heat treatment under the following conditions were measured in the same manner as in (i) and (ii) above. (Wet heat treatment conditions) Equipment used: PR-3KP (manufactured by Espec) Temperature: 75℃ Humidity: 90%RH Test time: 1,000 hours

[0165] [Examples 1 to 11, Comparative Examples 1 to 11] The mixture was fed from the first feed port of the extruder with the composition shown in Table 1. The mixture was obtained by mixing the following preliminary mixture (i) with other components in a V-type blender. That is, (i) is a mixture of the drip prevention agent of component E and the polycarbonate resin of component A, which was homogeneously mixed in a polyethylene bag by shaking the entire bag so that component E was 2.5% by weight. The amount of the mixture fed was precisely measured with a weighing machine [CWF manufactured by Kubota Corporation]. Extrusion was performed using a vented twin-screw extruder (TEX30α-38.5BW-3V manufactured by Japan Steel Works, Ltd.) with a diameter of 30 mmφ, and melt-kneaded at a screw rotation speed of 230 rpm, a discharge rate of 25 kg / h, and a vacuum degree of 3 kPa at the vent to obtain pellets. The extrusion temperature was 280°C from the first feed port to the die portion. A portion of the obtained pellets was dried in a hot air circulation dryer at 90 to 100°C for 6 hours, and then molded into ISO bending test pieces (ISO179) and UL test pieces using an injection molding machine at a cylinder temperature of 280°C and a mold temperature of 70°C.

[0166] The symbols used for each component in Table 1 are as follows: (Component A) A-1: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 22,400 made by a conventional method from bisphenol A and phosgene, manufactured by Teijin Ltd., Panlite L-1225WP (product name)) (B component) B-1: Butadiene-based core-shell type graft polymer (a graft copolymer with a core-shell structure in which the core is mainly made of butadiene rubber and the shell is mainly made of methyl methacrylate and styrene, manufactured by Mitsubishi Chemical Corporation, Metablen E-870A (product name)) (C component) C-1: A cyclic phenoxyphosphazene having a trimer content of k=1 of formula (15) of 100 mol%. C-2: A cyclic phenoxyphosphazene having a trimer content of k=1 of formula (15) of 98.5 mol%, a tetramer content of k=2 of 1 mol%, and a polymer content of k=3 or more of 0.5 mol. C-3: A cyclic phenoxyphosphazene having a content of 98 mol% of trimers of k=1 in the formula (15), a content of 1.5 mol% of tetramers of k=2, and a content of 0.5 mol of polymers of k=3 or more. C-4: The content of the trimer of k=1 of formula (15) is 70 mol%, and the content of the tetramer of k=2 is 70 mol%. A cyclic phenoxyphosphazene having a content of 20 mol % and a content of k=3 or more multimer of 10 mol %.

[0167] [ka]

[0168] (D component) D-1: Potassium perfluorobutanesulfonate (product name: Megafac F-114P, manufactured by Dai Nippon Ink Co., Ltd.) D-2: Potassium diphenylsulfonate (KSS (product name) manufactured by Arichem) D-3: Condensed phosphate ester (manufactured by Daihachi Chemical Industry Co., Ltd., product name CR-741) (E component) E-1: PTFE (Polyflon MPA FA500H (product name) manufactured by Daikin Industries, Ltd.) (Other Ingredients) STB: Phenol-based heat stabilizer (Octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, molecular weight 531, Irganox 1076 (product name) manufactured by BASF Japan Ltd.) WAX: Fatty acid ester release agent (Rikemal SL900 (product name) manufactured by Riken Vitamin Co., Ltd.)

[0169] [Table 1]

Claims

1. A flame-retardant polycarbonate resin composition comprising, relative to 100 parts by weight of (A) polycarbonate resin (component A), 1 to 8 parts by weight of (B) impact modifier (component B), 1 to 8 parts by weight of (C) phosphazene containing 98.5 mol % or more of phosphazene cyclic trimer (component C), 0.01 to 0.5 parts by weight of (D) organic sulfonic acid metal salt (component D), and 0.05 to 2 parts by weight of (E) drip prevention agent (component E).

2. 2. The flame-retardant polycarbonate resin composition according to claim 1, wherein component B is a graft copolymer obtained by graft polymerizing at least one compound containing a (meth)acrylic acid ester compound onto a butadiene rubber.

3. 3. The flame-retardant polycarbonate resin composition according to claim 1, wherein component D is an alkali metal salt of a perfluoroalkylsulfonic acid or an alkali metal salt of an aromatic sulfonic acid.

4. A molded article obtained by molding the resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Flame-retardant polycarbonate resin composition

    JP2004067881A

  • Polycarbonate resin composition and molded article

    JP2016084414A

  • Flame-retardant polycarbonate resin composition

    WO2020066535A1